Prevalence of work-related upper limbs symptoms (WRULS) among office workers - Rahman Z.A.; Atiya A.S. (2024)
An analytical cross-sectional study was carried out to determine the prevalence of work-related upper limbs symptoms (WRULS) among office workers and factors associated with it. A self-administered questionnaire was used to collect the information. A total of 463 (87.7%) office workers from selected government agencies participated in this study. The mean age of the respondents was 34.1 years (range = 18-55 years). Majority (91.6%) were Malay and female (72.8%), and 58.1% were from clerical group. Mean duration of work was 8.7 years. This study found that prevalence of WRULS was 33.0% (95% CI [confidence interval] = 28.8%, 37.3%). Computer users at work had 2.0 (95% CI = 1.1, 3.4) higher odds ratio of developing WRULS and those who used it for 5 hours and more per day had 7.5 (95% CI = 2.3, 24.2) higher odds ratio of developing WRULS. Hand-intensive hobbies and higher education were also found to be associated with WRULS. 2009 APJPH.